Relationship to the river: the case of the rural communities residing beside the Tembeling, Pahang and Muar Rivers - Abu Samah, Bahaman; Md. Yassin, Sulaiman; Hamzah, Azimi; Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi; Idris, Khairuddin (Canadian Center of Science and Education, 2013)
The present study attempts to identify the views of the rural community living near to Tembeling-Pahang-Muar river, regarding their relationship with the river. This study is qualitative in nature: a total of three focus group discussions were conducted among selected villagers from Kuala Tembeling, Kuala Tahan and Kundang Hulu villages. Four themes emerged from the analysis, namely sources of income, mode of transportation, less appreciation among the younger generation for the river, and the need for river development. Through the identification of this data, it is a hope that a broader understanding of the relationship between the local community and the river could facilitate river development programmes and strategies.